2019
DOI: 10.1590/s1677-5538.ibju.2018.0518
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of mirabegron in female patients with overactive bladder symptoms after surgical treatment for stress urinary incontinence

Abstract: Purpose To evaluate the efficacy and tolerability of mirabegron in females with overactive bladder (OAB) symptoms after surgical treatment for stress urinary incontinence (SUI).Materials and Methods The study was conducted with a prospective, randomized and double-blinded design. 62 patients over the age of 40 who met the inclusion-exclusion criterias of the study were enrolled and randomly divided into two groups as Group A (mirabegron 50mg) and B (solifenacin 5mg). Patients were compared based on efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Overactive bladder (OAB) is defi ned as urinary urgency, usually accompanied by frequency and nocturia, with or without urgency urinary incontinence (UUI) according to the International Continence Society (1). Many drugs such as oral anti-muscarinic agents and oral ß3 adrenoreceptor agonist (mirabegron) and fi rst-line conservative therapeutic options are commonly used for UUI and OAB, including electrical stimulation (ES), pelvic fl oor muscle (PFM) training and behavioral therapies such as lifestyle changes and bladder training (BT) (1)(2)(3)(4)(5)(6). BT involves a systematic voiding regimen to lengthen the interval between voids until an acceptable pattern has been restored (2,4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overactive bladder (OAB) is defi ned as urinary urgency, usually accompanied by frequency and nocturia, with or without urgency urinary incontinence (UUI) according to the International Continence Society (1). Many drugs such as oral anti-muscarinic agents and oral ß3 adrenoreceptor agonist (mirabegron) and fi rst-line conservative therapeutic options are commonly used for UUI and OAB, including electrical stimulation (ES), pelvic fl oor muscle (PFM) training and behavioral therapies such as lifestyle changes and bladder training (BT) (1)(2)(3)(4)(5)(6). BT involves a systematic voiding regimen to lengthen the interval between voids until an acceptable pattern has been restored (2,4,5).…”
Section: Introductionmentioning
confidence: 99%
“…and percutaneous ES (of the tibial nerve, electroacupuncture, etc.) (6). Intravaginal ES (IVES) is a conservative treatment option, described more than 40 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly responsible for promoting human detrusor relaxation and urine storage in the bladder [10] . Compared with anticholinergic agents, plenty of randomized controlled trials have reported that mirabegron could have better efficacy in monotherapy of the OAB symptoms [11–13] . However, they are also associated with specific side effects, including hypertension, constipation, dry mouth, tachycardia, and UTI [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Mete et al reported that symptoms including hypertension and palpitations can be relieved after withdrawal of the drug. 18 The quality of life among patients with other AE remained unaffected.…”
Section: Discussionmentioning
confidence: 97%
“… 17 Mirabegron has demonstrated significant efficacy and safety in the treatment of lower urinary tract symptoms (LUTs) following stress urinary incontinence surgery in women and OAB due to benign prostatic hyperplasia with bladder outlet obstruction in men. 18 , 19 However, its efficacy against symptoms of local side effects after TURBT with subsequent BCG immunotherapy remains unexplored.…”
Section: Introductionmentioning
confidence: 99%